A critical analysis of online Sesotho ICT terminology - Nteso, Thato Natasha (Rhodes University, Faculty of Humanities, School of Languages, 2013)
Information and Communication Technology (ICT) has taken over every aspect of our daily lives, from commerce to leisure and even culture. Today, mobile phones, desktop computers, hand-held devices, emails and the use of the internet have become a central part of our culture and society. ICT has made us a global society, where people can interact and communicate efficiently. In order for South Africa to be competitive in the global economy, it will need to develop a workforce with appropriate Information Technology skills. Of necessity, these skills will extend to using a computers and developing appropriate software and technical support skills (DOE, 2008). This thesis represents a critical analytical study in that it explores the online Sesotho Information and Communication Technology (ICT). It aims at analysing terminology development in this area. The study aims to determine how Sesotho and ICT correlate and how the linguistic aspect plays a role in online ICT terminology. The focus is not on creating new terms but to analyze the already existing ICT terms available, with regards to linguistic rules and principles and to critique if they are of quality. Furthermore, the thesis explores whether there are other strategies that can be used in the development of this terminology. It also seeks to determine if the terms are easily accessible to students and if they are used at all. Terms will be sourced from the Department of Arts and Culture ICT term list, and the focus will be on extracting only terms that have to do with computer literacy. Other online sources that list Sesotho equivalents will also be considered. The study also assesses the quality of the terms created by the Department of Arts and Culture (DAC) together with the Department of Communications (DOC) for a multilingual ICT terminology list. Furthermore, the thesis explores whether the Sesotho equivalents adhere to the linguistic rules and principles of the language. The other question asked is whether the terms are used by the intended users and if they are easily accessible to the speakers of the language. This entire aspect of the thesis speaks to the notion of the intellectualization of African languages and in this case Sesotho in particular. Not only does the thesis engage with computer literacy terminology, it also presents a detailed literature review of studies and work that has been done in this field. The thesis engagement is also done by linking the backdrop of the history of Sesotho and the Basotho peoples.
Keywords: Information technology -- Study and teaching -- South Africa; Sotho language -- Terms and phrases; Sotho language -- Orthography and spelling